The THE INFLUENCE OF PRINCIPAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND EMOTIONAL INTELLIGENCE THROUGH JOB SATISFACTION ON THE PERFORMANCE OF PUBLIC HIGH SCHOOL TEACHERS IN SAMALANGA DISTRICT, BIREUEN REGENCY: Nazaruddin dan Dr. Zainuddin Iba - Win, admin (LPPM-UNIKI, 2020)
This study aims to examine the factors that influence teacher performance, with job satisfaction as an intermediate variable. The research object was 50 public high school teachers in Samalanga District, Bireuen Regency. The research instrument used a questionnaire, and the method of analysis with a path analysis approach. The results showed that 1). There is an influence of thePrincipal Leadership on teacher job satisfaction of 17.74%. 2). There is an influence of organizational culture on teacher job satisfaction by 18.09%. 3). Teacher's emotional intelligence has a direct effect on teacher job satisfaction by 15.28%. 4). Job satisfaction also affects performance by 30.58%. 5). The influence of principal leadership on teacher performance through job satisfaction is 16.92%. 6). The influence of organizational culture on teacher performance through job satisfaction is 16.70%, and 7). The effect of teachers' emotional intelligence on teacher performance through job satisfaction is 15.59%.